Ferritinophagy/ferroptosis: Iron‐related newcomers in human diseases - Tang, Mingzhu; Chen, Zhe; Wu, Di; Chen, Linxi (Journal of cellular physiology, 2018)
Nuclear receptor coactivator 4 mediated ferritinophagy is an autophagic phenomenon that specifically involves ferritin to release intracellular free iron. Ferritinophagy is implicated in maintaining efficient erythropoiesis. Notably, ferritinophagy also plays a central role in driving some pathological processes, including Parkinson’s disease (PD) and urinary tract infections. Some evidence has demonstrated that ferritinophagy is critical to induce ferroptosis. Ferroptosis is a newly nonapoptotic form of cell death, characterized by the accumulation of iron‐based lipid reactive oxygen species. Ferroptosis plays an important role in inhibiting some types of cancers, such as hepatocellular carcinoma, pancreatic carcinoma, prostate cancer, and breast cancer. Conversely, the activation of ferroptosis accelerates neurodegeneration diseases, including PD and Alzheimer’s disease. Therefore, in this review, we summarize the regulatory mechanisms related to ferritinophagy and ferroptosis. Moreover, the distinctive effects of ferritinophagy in human erythropoiesis and some pathologies, coupled with the promotive or inhibitory role of tumorous and neurodegenerative diseases mediated by ferroptosis, are elucidated. Obviously, activating or inhibiting ferroptosis could be exploited to achieve desirable therapeutic effects on diverse cancers and neurodegeneration diseases. Interrupting ferritinophagy to control iron level might provide a potentially therapeutic avenue to suppress urinary tract infections. Nuclear receptor coactivator 4 (NCOA4)‐mediated ferritinophagy is an autophagic phenomenon that specifically involves ferritin to release intracellular free iron. Ferritinophagy plays a central role in maintaining efficient erythropoiesis and driving urinary tract infections. Ferritinophagy is critical to induce ferroptosis, a newly nonapoptotic form of cell death that inhibits some types of cancers and accelerates neurodegenerative diseases including Parkinson’s disease (PD) and Alzheimer’s disease (AD).